MET exon 14 juxtamembrane splicing mutations: clinical and therapeutical perspectives for cancer therapy - Pilotto, Sara (Ann Transl Med, 2017)
The MET proto-oncogene plays crucial roles in cell growth and proliferation, survival and apoptosis, epithelial-mesenchymal transition (EMT) and invasion, potentially conditioning the development and progression of the carcinogenesis process. The MET-associated aberrant signaling could be triggered by a variety of mechanisms, such as mutations, gene amplification, increased gene copy number and Met/HGF protein expression. Among the various MET alterations, MET exon 14 splicing abnormalities, causing the loss of the Met juxtamembrane (JM) domain, recently emerged as a new potential oncogenic driver and have been identified and validated across different cancer and histology subtypes. Moreover, this aberration was found to be mutually exclusive with other recognized drivers, thus strongly nominating its potential oncogenic role. Recently, the clinical activity of anti-Met-targeted therapy was demonstrated particularly in patients harboring MET exon 14 skipping lung cancer, resulting in a renewed enthusiasm to further test MET precision therapy in prospective trials. In this review, the key preclinical and clinical data regarding MET exon 14 skipping splicing variants as an actionable genomic aberration in cancer are described, and the perspectives deriving from the validation of such alteration as a potential target, which may further allow driving the therapeutic approach in this molecularly selected patients’ subgroup, are explored.